RAFT-mediated polymerization-induced self-assembly of poly(ionic liquid) block copolymers in a green solvent - Yang Yongqi; Ren Zekai; Li Xiawei; Zhao Enhao; Luo Xin; Yan Youjun; Gao Hongyan; Feng Lijuan (e-Polymers)
Synthesis of the poly(N,N-dimethylacrylamide)-b-poly(1-alkyl-3-(4-vinylbenzyl)imidazolium tetrafluoroborate) (PDMA43-b-PILx) block copolymers prepared by RAFT ethanol dispersion polymerization at 70°C.